Evaluation of Clinical and Ultrasonographic Parameters in Psoriatic Arthritis Patients Treated with Adalimumab: A Retrospective Study. (9th May 2012) - Teoli, M.; Zangrilli, A.; Chimenti, M. S.; Talamonti, M.; Bavetta, M.; Graceffa, D.; Perricone, R.; Chimenti, S.
Abstract : Objectives . The aim of this study was to evaluate clinical and US-PD parameters in PsA during adalimumab treatment. Methods . A retrospective study has been conducted in forty patients affected by moderate-to-severe peripheral PsA. Clinical, laboratory, and US-PD evaluations were performed at baseline, after 4, 12, and 24 weeks of treatment. They included erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), visual analogue scale (VAS), Health Assessment Questionnaire (HAQ) modified for Spondyloarthritis, Psoriasis Area Severity Index (PASI) score, the 28-joint Disease Activity Score (DAS 28), and US-PD assessment. US-PD findings were scored according to a semiquantitative scale (ranging 0–3) for synovial proliferation (SP), joint effusion (SE), bone erosions (BE), and PD. Results . Data obtained for clinical, laboratory findings and US-PD evaluation showed statistical significant improvement in all the measures performed except for BE. A significant parallel decrease in SE, SP, and PD values were demonstrated. Conclusion . This study demonstrated that US-PD is a valid technique in monitoring the response to adalimumab in moderate-to-severe PsA.